DESENTRALISASI ASIMETRIS DALAM RESOLUSI KONFLIK SEPARATISME ACEH DAN PAPUA - Dilla Janu Istanti; Anita Febriani; Netty Ariani (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2021)
Separatist conflicts in Indonesia have occurred in Aceh and are still volatile in Papua. The separatist conflict has entered into a vertical conflict involving the state and separatist groups carrying out rebellions. Rebellions in Aceh were instigated by the Free Aceh Movement (GAM) to gain independence from Indonesia between 1976 and 2005. Riots in Papua also occurred as a result of rebellions by armed separatist groups, the Free Papua Organization (OPM). Various steps have been taken by the government to resolve the conflict. One of the ways that the government has done is by implementing an asymmetric decentralization system. Asymmetric decentralization imposes special powers on certain regions because it is considered to be an alternative to solve problems in the relationship between the central government and local governments. This paper aims to examine the extent to which asymmetric decentralization has had an effect on resolving separatist conflicts in Aceh and Papua